Influência do 4-Hidroxi-2,2´,6,6´-tetrametilpiperidina-1-oxil (Tempol) sobre a formação de espécies reativas do oxigênio e de armadilhas extracelulares e na resposta microbicida de neutrófilos humanos contra Mycobacterium tuberculosis - Cerdeira, Cláudio Daniel (2015)
Mycobacterium tuberculosis (Mtb), the main cause of tuberculosis (TB), remains as a serious public health problem, chiefly in low- to middle-income countries. It is estimated that about one-third of the world's population has latent TB, with about eight million new cases and roughly three million deaths each year from TB. The innate immune response following Mtb infection plays a crucial role in preventing the onset of active TB, as well as its course. Thus, phagocytes-derived reactive oxygen/nitrogen species (ROS/RNS) during the oxidative burst (e.g., generated by neutrophils) are essential to an effective response to the pathogen. The indiscriminate use of antioxidant supplements, currently very common among the population, or their use as adjuvant therapy during TB treatment, could compromise the immune response to Mtb accordingly potentially increasing the host's susceptibility to Mtb/TB. In this context, the aim of this study was to investigate the ex vivo effect of the cyclic nitroxide tempol (4-hydroxy-2,2,6,6-tetra-methyl-1-piperidinyloxy), an antioxidant with superoxide dismutase mimetic properties, on the microbicide response of neutrophils against M. tuberculosis. Human neutrophils were isolated from venous blood of healthy volunteers by Ficoll density gradient centrifugation. To assess the oxidative burst in the absence or presence of Tempol, M. tuberculosis H37Ra (ATCC 35177) was incubated at 37 ° C with neutrophils at multiplicity of infection (MOI) ranging from 1 to 100. ROS generation (O2•-) by neutrophils was evaluated by using the cytochrome c reduction assay. The total and extracellular ROS were determined using the luminol- and Isoluminol-amplified chemiluminescence assay. Complementarily, the killing assay was performed to check the total microbicide capacity of neutrophils treated or not with Tempol. In this test, the "two-step" protocol was adopted in which, Mtb was incubated with neutrophils (for 10, 30, and 90 min at 37 °C) and, by differential centrifugation (100 x g 5 min) and lysis of neutrophils with H2O pH 11, the intracellular and extracellular mycobacteria were incubated for 21 days at 37 ° C and, mycobacteria were quantified and results the ensuing reported as number of Colony Forming Units (CFU). Through this protocol, were calculated the phagocytosis (Kp) and intracellular killing (Kk) rates for M. tuberculosis. The possible toxic activity of Tempol was evaluated on neutrophils and, was observed that 500 µM tempol was not cytotoxic. The oxidative burst of neutrophils against Mtb was significantly decreased in the presence of 450 µM Tempol, for all evaluated oxidants (p < 0.05). Treatment of neutrophils with 450 µM Tempol decreased the total microbicidal activity against M. tuberculosis, since colony-forming units of these mycobacteria in the treated group were significantly higher than those for the untreated group (p < 0.05). Strikingly, Tempol (450 µM) decreased the kk of neutrophils, but had no effect on their kp. This study provides insights of the influence of antioxidants on the immune response to M. tuberculosis, so that clinical implications for the prevention and treatment of TB should take into account these findings.